Learning analytics for reducing student dropout in digital video platforms - Al-Hafdi,Fahad Saleem; Alhalafawy,Waleed Salim (PeerJ Computer Science, 2026)
Digital video platforms (DVPs) are experiencing increased popularity as educational resources, yet they face challenges in achieving sustainability due to dropout among students. This research aims to examine the effect of Learning Analytics (LA) on reducing dropout in a DVP environment. A quasi-experimental design was employed to compare experimental and control groups, each consisting of 30 sixth-grade students. The experimental group utilized DVP with LA, while the control group used DVP without LA. LA data included the completion percentage of full video viewing, time spent watching the video, correct and incorrect answers to the questions embedded within the video, number of views for each segment of the video and date and time of the last video viewing. A dropout scale was developed, encompassing three dimensions: satisfaction, engagement, and continuity. The results showed a significant reduction in dropouts in the LA group. LA also contributed to improving student satisfaction, engagement, and continuity within the DVP environment. The results also showed correlations and mutual influence between satisfaction, engagement, and continuity.
Keywords: Learning analytics (LA); Digital video platforms (DVPs); Dropout